Pericoronal Follicles of Asymptomatic Impacted Teeth: A Radiographic, Histomorphologic, and Immunohistochemical Study. (23rd January 2012) - Villalba, Laura; Stolbizer, Federico; Blasco, Fabián; Mauriño, Néstor Raúl; Piloni, María Julia; Keszler, Alicia
Abstract : Objective . To associate radiographic and histopathological features of pericoronal follicles (PFs) of asymptomatic impacted teeth and evaluate cell proliferation and apoptosis in the epithelium. Study Design . Epithelium and mesenchyme of radiographically normal (NPF ≤ 2.5 mm) and hyperplastic (HPF 2.6 to 5 mm) PF (n = 140 ) were studied histologically. Cell proliferation (PI) and epithelial apoptosis were evaluated by Ki-67 and bcl-2 expression in 14 NPFs and 10 dentigerous cysts (DCs). Results . Radiographically, 127 were NPFs and 13 were HPFs; 87.8% of total PFs exhibited epithelium on the surface. Reduced enamel epithelium was observed in 78 (61.4%) NPFs and 6 (46.2%) HPFs, squamous metaplasia in 17 (13.4%) NPFs and 4 (30.8%) HPFs, and cystic epithelium in 15 (11.8%) NPFs and 3 (23%) HPFs. Mean PI was 1.97 ± 1.25 and 7.97 ± 1.74 in the epithelial component of NPF and DC, respectively; bcl-2 positive expression was observed in 9 (64.3%) NPFs and 7 (70%) DCs. Conclusion . The scant epithelial remnant proliferation could imply low risk for development of odontogenic pathologies in the absence of an additional stimulus.